Overview on the Phase Conjugation Techniques of the Retrodirective Array - Lei Chen; Yu Chun Guo; Xiao Wei Shi; Tian Ling Zhang (International Journal of Antennas and Propagation)
This paper presents an overview on the phase conjugation techniques of the retrodirective antenna array. The concepts, advantages, and disadvantages of phase conjugation techniques are introduced. The self-phasing characteristic and technical difficulties of the array are presented as well as their structures and applications. Further researches in this area are presented finally.